Determinants of Earnings Per Share and Price Earnings Ratio to Share Prices in LQ45 Indices Companies on the Indonesia Stock Exchange - Vikka Putri; M. Agustiswan Saputra (Politeknik Negeri Madiun, 2023)
This study aims to determine the effect of Earning Per Share and Price Earnings Ratio on Stock Prices. The population in this study are Go-Public companies from the LQ45 Index listed on the Indonesia Stock Exchange during the 2017-2019 period. The sample selection technique in this study is purposive sampling, 36 companies have been acquired that meet the criteria for the study sample. The analytical tool used in this study is SPSS version 26. The results show that the simultaneous Earning Per Share and Price Earnings Ratio have a significant effect on the dependent variable, namely the Share Price at LQ45 Index Companies Listed on the Indonesia Stock Exchange for the 2017-2019 period. Partially, Earning Per Share and Price Earnings Ratio have a significant positive effect on Share Prices at LQ45 Index Companies Listed on the Indonesia Stock Exchange for the 2017-2019 period.